Association of People Factors with Successful Enterprise Architecture Implementation - Azaliah Abu Bakar, Nur; Sumarni Hussien, Surya (International Journal of Engineering and Technology, 2018)
Many organizations are facing problem in Enterprise Architecture Implementation as it fails to meet expectations.  While much has been written about the success factors related to EA framework, EA tools, and business-IT alignment process, there are few empirical investigations focusing on the people factors.  Therefore, this paper aims to investigate the association of people factors with successful EA implementation by identifying seven people factors from the literature.  A quantitative survey was conducted to assess the hypothesis that these seven people factors are associated with the successful EA implementation.  The analysis reveals that only five factors are associated with the success of EA implementation, while two are not.  Based on the result, this study highlighted that it is important to analyze the people factors in details rather than one whole factor because each of the people factors identified has their own uniqueness and success elements